Genetic characterization of Entamoeba histolytica reveals a significant association of parasite genotype with disease outcome - Das, Koushik; Chowdhury, Punam; Nozaki, Tomoyoshi; Ganguly, Sandipan (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2016)
Amoebiasis caused by the enteric parasite Entamoeba histolytica has variable disease outcomes. The association between parasite genotypes and outcome of amoebic infection still remains obscure and requires to be explored. Genetic characterization of clinical isolates is certainly a useful method to explore this relation. E. histolytica isolates from different disease outcomes has been genetically characterized based on the widely used repetitive marker, Serine rich E. histolytica protein gene (Srehp). Genetic organizations of our study isolates are unique in compare to previous reports. Most of the identified repeat patterns are outcome specific. Significant association between parasite genotypes and outcome of amoebic infection has also been established.